Odpowiedź :
[tex]log_216=4\\2^x=16\\2^x=2^4\\x=4[/tex]
[tex]log_3243=5\\3^x=243\\3^x=3^5\\x=5[/tex]
[tex]log_2\frac1{16}=-4\\2^x=\frac1{16}\\2^x=16^{-1}\\2^x=2^{-4}\\x=-4[/tex]
[tex]log_4\frac1{256}=-4\\4^x=\frac1{256}\\4^x=256^{-1}\\4^x=4^{-4}\\x=-4[/tex]
[tex]-2log_{\frac12}4=log_{\frac12}(4^{-2})=log_{\frac12}\frac1{16}=4\\(\frac12)^x=\frac1{16}\\(\frac12)^x=(\frac12)^4\\x=4[/tex]
[tex]4log_{\frac19}\frac13=log_{\frac19}(\frac13)^4=log_{\frac19}\frac1{81}=2\\(\frac19)^x=\frac1{81}\\(\frac19)^x=(\frac19)^2\\x=2[/tex]
[tex]25^{log_53}=(5^2)^{log_53}=5^{2log_53}=5^{log_53^2}=3^2=9\\\text{Z wzoru: } a^{log_ab}=b[/tex]
[tex]9^{log_36}=(3^2)^{log_36}=3^{2log_36}=6^2=36[/tex]
[tex]log_22\sqrt2=\frac32\\2^x=2\sqrt2\\2^x=\sqrt{2*2*2}\\2^x=\sqrt{2^3}\\2^x=2^{\frac32}\\x=\frac32[/tex]
[tex]log_525\sqrt5=\frac52\\5^x=25\sqrt5\\5^x=5^2*5^{\frac12}\\5^x=5^{2+\frac12}\\5^x=5^{\frac52}\\x=\frac52[/tex]
[tex]log_2\frac{\sqrt2}2=-\frac12\\2^x=\frac{\sqrt2}2\\2^x=\sqrt2:2\\2^x=2^{\frac12}:2^1\\2^x=2^{\frac12-1}\\2^x=2^{-\frac12}\\x=-\frac12[/tex]
[tex]log_39\sqrt3=\frac52\\3^x=9\sqrt3\\3^x=3^2*3^{\frac12}\\3^x=3^{2+\frac12}\\3^x=3^{\frac52}\\x=\frac52[/tex]
[tex]log_39\sqrt{27}=log_39*3\sqrt3=log_327\sqrt3=\frac72\\3^x=27\sqrt3\\3^x=3^3*3^{\frac12}\\3^x=3^{3+\frac12}\\x=\frac72[/tex]
[tex]log_3\frac{\sqrt3}{27}=-\frac52\\3^x=\frac{\sqrt3}{27}\\3^x=\sqrt3:27\\3^x=3^{\frac12}:3^3\\3^x=3^{\frac12-3}\\x=-\frac52[/tex]
[tex]log1000\sqrt[3]{10}=\frac{10}3\\10^x=1000\sqrt[3]{10}\\10^x=10^3*10^{\frac13}\\10^x=10^{3+\frac13}\\x=\frac{10}3[/tex]
[tex]log100\sqrt[4]{100}=\frac52\\10^x=100\sqrt[4]{100}\\10^x=10^2*100^{\frac14}\\10^x=10^2*(10^2)^{\frac14}\\10^x=10^2*10^{\frac12}\\10^x=10^{2+\frac12}\\x=\frac52[/tex]
[tex]log\frac{\sqrt[3]{10}}{100}=-\frac53\\10^x=\frac{\sqrt[3]{10}}{100}\\10^x=\sqrt[3]{10}:100\\10^x=10^{\frac13}:10^2\\10^x=10^{\frac13-2}\\x=-\frac53[/tex]
Przydatne wzory!
[tex]log_ab=c \to a^c=b\\nlog_ab=log_ab^n\\a^{log_ab}=b\\a^{-n}=\frac1{a^n}\\a^{\frac{n}m}=\sqrt[m]{a^n}\\a^b*a^c=a^{b+c}\\\frac{a^b}{a^c}=a^{b}:a^c=a^{b-c}\\(a^b)^c=a^{b*c}[/tex]